Simultaneous detection of assembly and disassembly of multivalent HA tag and anti‐HA antibody in single in‐capillary assay. Issue 15 (6th May 2016) - Wang, Jianhao; Qin, Yuqin; Qin, Haifang; Liu, Li; Ding, Shumin; Teng, Yiwan; Ji, Junling; Qiu, Lin; Jiang, Pengju
Abstract : Herein, we have developed an in‐capillary assay for simultaneous detection of the assembly and disassembly of the multivalent HA tag peptide and antibody. HA tag with hexahistidine at C terminus (YPYDVPDYAG4 H6, termed YPYDH6 ) was conjugated with quantum dots (QDs) by metal‐affinity force to form a multivalent HA tag (QD‐YPYDH6 ). QD‐YPYDH6 and monoclonal anti‐HA antibody (anti‐HA) were sequentially injected into the capillary. They were mixed and assembled inside the capillary. The reaction products were online discriminated and detected by fluorescence coupled capillary electrophoresis (CE‐FL). For the in‐capillary assay, the binding efficiency of the multivalent HA tag and antibody on was influenced by the molar ratio and injection time. Such novel assay could even give out the self‐assembly kinetic constant of QDs and YPYDH6 as K D of 34.1 μM with n (binding cooperativeness) of 2.2 by Hill equation. More importantly, the simultaneous detection of the assembly and imidazole (Im) induced disassembly of the QD‐YPYDH6 ‐anti‐HA complex was achieved in a single in‐capillary assay. Our study demonstrated a new method for the online detection of antigen‐antibody interactions.